“Las niñas también juegan con carritos” la mujer en la gerencia: el caso del Perú - Adaniya, Ana Rosa (1993)
The purpose of this research is to determine whether there are differences between managers’ perceptions about the characteristics of a successful manager. It is based on Schein’s studies of gender role stereotypes and the characteristics required to be considered a successful manager. The hypotheses, one for men and one for women, are that managers will perceive that successful ones have attitudes, characteristics and temperaments that are more commonly attributed to men in general than to women in general. The slightly modified Schein Descriptive Index questionnaire to a sample of 268 managers working in Lima. Interclass correlation coefficients (r’) were calculated from two random group analysis of variance of the 92 descriptive items. In conclusion, it is found that while the hypothesis in confirmed in male managers, the same is not true in female managers, who perceive thar both men and women have characteristics of successful managers. Another finding is that age and years of experience moderate the perceptions of women, while the level of education moderates those of men.